A Multiplexed, Gradient‐Based, Full‐Hydrogel Microfluidic Platform for Rapid, High‐Throughput Antimicrobial Susceptibility Testing. Issue 5 (1st June 2017) - Liu, Zhengzhi; Sun, Han; Ren, Kangning
Abstract: Antimicrobial resistance has become an immediate threat to modern healthcare systems as it continues to spread across the globe. As development of novel antibiotics stalls, preserving the effectiveness of existing agents has become a priority. One of the major driving forces behind antimicrobial resistance is the misuse and overuse of antibiotics, often a result of data on the susceptibility of pathogens not being obtained in a convenient and timely manner, a need that conventional antimicrobial susceptibility testing struggles to meet. Here, a hydrogel microfluidic platform is reported for antimicrobial susceptibility testing purposes, capable of handling real samples and yielding results within 2.5 h of culture. By using a multiplayer design with channels crossing overhead of each other, multiple experiments, either one‐ or two‐dimensional, can be staged on the same device. Bacteria grown on the surface of the hydrogel can be easily visualized with standard Gram staining after being transferred onto a glass slide. Coupled with software‐based image analysis, the system can yield a variety of useful information on bacterial susceptibility and the effects of drugs, such as minimum inhibitory concentration and morphological changes in bacteria, either individually or in combination. Compared to conventional testing methods, this system requires less labor, reagents, and equipment to operate, and has significantly higher speed and efficiency. Abstract : Micromanagement is a grower ! A hydrogel microfluidic platform for rapid antimicrobial susceptibility testing on real samples is disclosed. Two sets of channels crossing overhead allowed multiple gradient zones to be formed by diffusion and used to test different drugs and their combinations (see figure). Cells were visualized by Gram staining after being transferred to a microscope slide and image analysis was performed to yield quantitative antimicrobial susceptibility test results.